Pengaturan Kewenangan Notaris Melakukan Pengesahan Fotokopi Surat dengan Aslinya - Atmaja, I Dewa Gede Ngurah Anandika (Acta Comitas, 2019)
Article 15 paragraph (2) letter d UUJN-P concerning the authority of Notaries to approve the suitability of a photocopy with the original letter there is an obscurity of legal norms which gives rise to multiple interpretations in terms of validating the suitability of photocopies made by a Notary in accordance with the original letter which does not provide clarity of understanding of how the Notary to do matching and any letter that can be validated by a Notary. The writing of this journal aims to develop Notary Legal Science that examines the authority of the Notary to validate the suitability of the photocopy with the original letter. The study of scientific journal writing uses a type of normative research that departs from the obscurity of legal norms Article 15 paragraph (2) letter d UUNJ-P regarding the authority of a Notary to authorize the compatibility of a photocopy with the original letter. The results of this journal research is legal certainty Article 15 paragraph (2) letter d UUJN-P related to the authority of the Notary in validating the suitability of the photocopy with the original letter there is still a vague legal norm that does not provide clarity of understanding of how the Notary does the matching and what letter matching validation can be done. The authority of the Notary in ensuring the correctness of the suitability of the photocopy with the original letter whether or not having the authority in the study of the author is a Notary having the authority stipulated in the provisions of Article 15 paragraph (2) letter d UUJN-P but in this case it needs to be corrected in the future considering UUJN-P is not provide legal certainty to the extent of the authority of the Notary in validating the suitability of the photocopy with the original letter. Berdasarkan Pasal 15 ayat (2) huruf d Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Atas Undang Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris mengenai kewenangan Notaris melakukan pengesahan kesesuaian fotokopi dengan surat aslinya terdapat kekaburan norma hukum yang menimbulkan multitafsir dalam hal pengesahan kecocokan fotokopi yang dilakukan oleh Notaris sesuai dengan surat aslinya yang tidak memberikan kejelasan pemahaman tentang bagaimana cara Notaris untuk melakukan pencocokan fotokopi dengan surat asli dan apa saja yang dapat dilakukan oleh Notaris untuk mengetahui keaslian fotocopi dokumen yang diberikan penghadap dalam melaksanakan pengesahan pencocokan sesuai dengan aslinya.Tujuan penulisan jurnal ini guna mengembangkan Ilmu Hukum Kenotariatan yang mengkaji tugas Notaris melakukan pengesahan kecocokan fotokopi dengan surat aslinya. Penelitian penulisan jurnal ilmiah ini menggunakan metode penelitian  normatif yang berawal dari adanya kekaburan norma hukum Pasal 15 ayat (2) huruf d UUNJ-P mengenai kewenangan Notaris untuk melakukan pengesahan kecocokan fotokopi dengan surat aslinya. Hasil penelitian jurnal ini adalah kepastian hukum Pasal 15 ayat (2) huruf d UUJN-P terkait kewenangan Notaris dalam mengesahkan kesesuaian fotokopi dengan surat aslinya masih terdapat kekaburan norma hukum. Kekaburan tersebut tidak memberikan kejelasan pemahaman tentang bagaimana cara Notaris dapat mengetahui pencocokan fotocopy surat yang akan dicocokan dapat dikatakan asli. Kewenangan Notaris dalam memastikan kebenaran kesesuaian fotokopi surat dengan surat aslinya tertdapat dalam ketentuan Pasal 15 ayat (2) huruf d UUJN-P akan tetapi hal ini kedepannya perlu dilakukan pembenahan mengingat dalam pasal tersebut tidak memberikan kepastian hukum sejauh mana kewenangan Notaris dapat melakukan pengesahkan persesuaian fotokopi dengan surat aslinya.